Iranian Osteoporosis Research Network: Background, Mission and Its Role in Osteoporosis Management - HR Aghaei Meybodi; R Heshmat; Z Maasoumi; A Soltani; A Hossein-nezhad; AA Keshtkar; A Bahrami; R Rajabian; I Nabipour; GH Omrani; M Pajouhi; B Larijani (Tehran University of Medical Sciences, 2008)
"nBecause of increase in elderly population, osteoporosis appears to become as a major public health issue in developing countries as in Iran. In order to obtain a clearer picture of osteoporosis in Iran, studies on different aspect of osteoporosis especially national projects about epidemiology and burden of disease, are required. Coordinating research programs is possible only by establishing a research network, so the national osteoporosis research network was suggested by Endocrinology and Metabolism Research of Tehran University of Medical Sciences. Iranian Osteoporosis Research Network (IORN) was established in 2002 by approval of Deputy for Research and the National Advisory Committee on Non-communicable Diseases of Ministry of Health and Medical Education of Iran. At first, five centers of Medical Sciences Universities and Research Centers in addition to the EMRC, participated in this project. Gradually more centers joined to the network and the numbers of IORN members are now 41 persons from 21 universities and research centers. IORN has had several activities: 1) Research projects, from among them are Iranian Multi-center Osteoporosis Study (IMOS) and Hip Fracture Registry Project (HFRP) in Iran 2) Educational activities with the aim of preventing osteoporosis and its related fractures 3) Establishment of osteoporosis clinic.  In summery osteoporosis is an important public health issue especially in developing countries because of increasing in elderly population. Close relationship between academic and research centers through the IORN membership provided possibility of designing and applying national research projects on epidemiology and burden of osteoporosis.